On the Teaching of Philosophy in Brazilian Basic Education: Reflections from Kantian Enlightenment and Adulthood - Guimarães, Odair; Silva, Matheus Felipe [UNESP] (Universidad Nacional del Litoral, 2023)
Evaluating the role of the teaching of Philosophy in basic education requires contextualizing the problem and reviewing its history, and it is necessary to describe its historicity and its advances and setbacks, since Brazilian education has undergone several reforms over the years, but these were designed to meet the needs of each period. We therefore propose a reconstruction of the insertion of the teaching of Philosophy in national basic education, understanding that this, at the end of this formative process, culminates with the legal assumption of the civil majority. In this sense, we draw parallels with Kantian philosophy with regard to the age of majority and the Enlightenment.
Sobre la enseñanza de la Filosofía en la educación básica brasileña: reflexiones desde la ilustración kantiana y la mayoría de edad
Sobre o ensino de Filosofia no ensino básico brasileiro: reflexões a partir do esclarecimento e da maioridade kantianos
Keywords: Adulthood; Enlightenment; Kant; Philosophy; Teaching